2007
DOI: 10.1021/ol701741e
|View full text |Cite
|
Sign up to set email alerts
|

Viologen-Based Redox-Active Ionic Liquid Crystals Forming Columnar Phases

Abstract: Viologens possessing three alkoxy chains at each terminal self-organize into columnar liquid-crystalline phases through nanophase segregation and electrostatic interactions. These viologens are redox-active and susceptible to two consecutive electrochemical reductions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 66 publications
1
56
0
Order By: Relevance
“…Influence of counterion on the mesomorphic behavior and photophysical properties of columnar pyridinium ionic liquid crystals derived from 4-hydroxypyridine OC 12 …”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…Influence of counterion on the mesomorphic behavior and photophysical properties of columnar pyridinium ionic liquid crystals derived from 4-hydroxypyridine OC 12 …”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…The WAXS experiments further demonstrate that the rectangular columnar structure consists of microphase-separated crystalline rod domains and the amorphous coil domains (Figure 3(b)). [25][26][27][28] It is observed that on heating, the hexagonal ordered structure transforms into a 2-D rectangular columnar structure, hence, this result suggests that the hexagonal structure of molecule 7 in the crystalline state is an intermediate structure between the lamellar and 2-D rectangular columnar structures. Furthermore, an interesting point to be noted is that the peak intensity associated with the (002) reflection appears to be the most intense (Figure 3(a)), implying that the fundamental structure is lamellar.…”
Section: Resultsmentioning
confidence: 99%
“…Columnar phases could be obtained for liquid crystals bearing two 3,4,5-tris(alkoxy) benzyl units attached to the 4,4'-bipyridinium moiety [61]. The viologen product bearing six octyloxy chains shows a hexagonal columnar (Col h ) phase, while the analogues with longer alkoxy chains (12 or 16) show rectangular columnar (Col r ) phases.…”
Section: 4'-bipyridinium-based Ionic Liquid Crystalsmentioning
confidence: 99%